Ethics in Islamic finance - Abdullah Haron; Muhammad Adli Musa; Ahmad Zakirullah M. Shaarani (IBFIM, 2013)
In enforcing ethics in Islamic finance, ethical education, regulatory regimes and constant supervision need to work together in realizing its objective. One of the goals of regulations is to ensure high ethical standards and fairness in the markets. The code of conducts introduced by the authorities serves as the enforcement mechanism to guide the professional to act ethically. Standard setting organisations have provided some guidance to ensure that Shari'ah rules and principles are complied at all times, transparency and market discipline through disclosures and appropriate moral conduct expected from the employees of the institutions. In conclusion, holding up ethical values in Islam is the utmost important thing in addressing the various issues that we are facing today, including finance.